Censuses in the Ottoman Period and Analysis of These Censuses - Mehmet Güneş (Gazi Akademik Bakış)
Since first periods of The Ottoman State, censuses had been made especially to determine people responsible for tax and in military age. Censuses handled in these purposes shows different features according to periods and preparation aims. At first times, registers were made to see current tax potential in the country related to fief system and books were organized in result of these works. Register works were started to be exercised as avariz counts when fief system lost its importance and counts continued in that way during 18. century. Forms of count works started to change with new improvements in 19. century. In this connection although a census was made at first in years of 1828-29, it wasn’t completed because of war. Hereafter male population in the country was tried to be determined by a general census in 1830- 31. Polling was exercised in the country regularly after these censuses and prepared books were sent to the center. Furthermore in some periods, censuses were performed to see population and wealth of people. This article about mentioned subjects, examines last censuses of the Ottoman period, the books prepared in result of these censuses and preserved until today; explaines the foundations housing mentioned books today, numbers and certain features of books; also exhibits different kinds of records related to censuses orderly. Eventually this work aims to be guide for researchers, explaining register and census books and especially population records of 19. century.